Inflammatory Bowel Disease in Children - Harum, Nabila Annisa; Syahbani, Primadita; Wibowo, Idznika Nurannisa (The Indonesian Society of Pediatric Gastroenterology, Hepatology, and Nutrition, 2024)
Background: Pediatric inflammatory bowel disease (IBD) is an idiopathic inflammatory disease in the digestive system with chronic onset, which often presents with unique and atypical phenotypes. This study aimed to dissect the important features of inflammatory bowel disease in children Discussion: The two types of inflammatory bowel disease (IBD) are ulcerative colitis (UC) and Crohn’s disease (CD). In children, IBD may exhibit classic symptoms such as weight loss, abdominal pain, and bloody diarrhea. However, many patient present with atypical symptoms such as isolated poor growth, anemia, or other extraintestinal manifestations. Early diagnosis of IBD in children is crucial as delayed diagnosis may lead to serious complications like bowel narrowing or abnormal connections, and stunted growth. The recommended initial evaluations in a pediatric patient with suspected IBD are complete blood test, stool examination, endoscopy and imaging. Furthermore, the aims of IBD treatment in children are to improve quality of life, relieve symptoms, promote normal growth, and prevent complications, all while minimizing medication side effects. Conclusion: Early diagnosis and treatment are essential in managing pediatric IBD. Additionally, addressing the disease's impact on bone health, growth, development, and psychosocial well-being is also crucial to achieve comprehensive management.